2018
DOI: 10.18203/2349-2902.isj20180800
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic ilioinguinal neurectomy in open inguinal hernia repair: a randomized control trial

Abstract: Background: Inguinal neuralgia is one of the important complications of hernia repair which occurs due to entrapment, neuroma or fibrotic reactions involving the ilioinguinal nerve. Hence the excision of ilioinguinal nerve should theoretically eliminate the possibility of inguinal neuralgia. But routine ilioinguinal neurectomy is still controversial and is not widely accepted. Hence a study was conducted to evaluate the effect of prophylactic ilioinguinal neurectomy in open inguinal hernia repair.Methods: A pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…For the remaining 31 studies, the full texts were obtained and reviewed. Sixteen studies were included [28–43], and 15 studies were excluded from the meta‐analysis (three were not randomized [44–46], six RCTs performed a short follow‐up [47–52], in three RCTs the timing of the follow‐up was different from 6 and 12 months [53–55], two RCTs used the sutureless Trabucco technique [56, 57], and one RCT analyzed the neurectomy of the iliohypogastric nerve [58]).…”
Section: Resultsmentioning
confidence: 99%
“…For the remaining 31 studies, the full texts were obtained and reviewed. Sixteen studies were included [28–43], and 15 studies were excluded from the meta‐analysis (three were not randomized [44–46], six RCTs performed a short follow‐up [47–52], in three RCTs the timing of the follow‐up was different from 6 and 12 months [53–55], two RCTs used the sutureless Trabucco technique [56, 57], and one RCT analyzed the neurectomy of the iliohypogastric nerve [58]).…”
Section: Resultsmentioning
confidence: 99%
“…Incidence of post-operative hypoesthesia and numbness at groin between the two groups at all post-operative follow up was found to be non-significant. Belagali et al(2018) [19] in their study of 60 patients with 30 patients each in nerve excision group and nerve preservation group found during vigorous activities, more group B patients had pain compared to group A patients at 4-month [5 (17%) vs. 15 (50%); p=0.006; Chisquare test] and 8-month follow-up [4 (13%) v/s 11 (37%) ;p=0.04] However, these results were not confirmed in a recent randomized controlled trial by Picchio et al [8] , who found similar incidence of chronic groin pain between ilioinguinal nerve excision group versus nerve preservation. Much controversy exists regarding which treatment to be followed for the inguinal nerves during hernia repair.…”
Section: Jmscr Vol||07||issue||03||page 704-710||march 2019mentioning
confidence: 99%
“…For the remaining 31 studies, the full texts were obtained and reviewed. Sixteen studies were included [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], and 15 studies were excluded from the meta-analysis (three were not randomized [44][45][46], six RCTs performed a short follow-up [47][48][49][50][51][52], in three RCTs the timing of the follow-up was different from 6 and 12 months [53][54][55], two RCTs used the sutureless Trabucco technique [56,57], and one RCT analyzed the neurectomy of the iliohypogastric nerve [58]).…”
Section: Trial Identificationmentioning
confidence: 99%